2021
DOI: 10.3389/fpsyt.2021.701420
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effect of Betel Quid Chewing on Brain Network Dynamics: A Resting-State Functional Magnetic Resonance Imaging Study

Abstract: Betel quid (BQ) is one of the most popular addictive substances in the world. However, the neurophysiological mechanism underlying BQ addiction remains unclear. This study aimed to investigate whether and how BQ chewing would affect brain function in the framework of a dynamic brain network model. Resting-state functional magnetic resonance imaging scans were collected from 24 male BQ-dependent individuals and 26 male non-addictive healthy individuals before and promptly after chewing BQ. Switching rate, a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…For example, Harlalka et al [ 84 ] found that patients with autism spectrum disorder showed a significant increase in dynamic variability (decreased temporal stability) in a wide range of brain network connections. Additionally, significantly decreased temporal stabilities of brain networks have been associated with both substance [ 85 ] and non-substance [ 59 ] addictions, suggesting that brain network instability may play an important role in the onset of these disorders.…”
Section: Research Progress On Possible Relationships Between the Temp...mentioning
confidence: 99%
“…For example, Harlalka et al [ 84 ] found that patients with autism spectrum disorder showed a significant increase in dynamic variability (decreased temporal stability) in a wide range of brain network connections. Additionally, significantly decreased temporal stabilities of brain networks have been associated with both substance [ 85 ] and non-substance [ 59 ] addictions, suggesting that brain network instability may play an important role in the onset of these disorders.…”
Section: Research Progress On Possible Relationships Between the Temp...mentioning
confidence: 99%
“…To calculate temporal variability of dFC, a widely used sliding-windows approach ( Long et al, 2020a ; Huang D. et al, 2021 ; Huang X. et al, 2021 ) was applied to segment the time series of all ROIs into a number of continuous time windows; in the primary analyses, a window width of 100 s and a step length of 6 s were used according to previous recommendations ( Sun et al, 2019 ; Long et al, 2020a ). The same as static FC, weighted adjacency matrices were computed in each time window to represent dFC during different time periods.…”
Section: Methodsmentioning
confidence: 99%
“…Data preprocessing was performed using the standard pipeline provided by the DPARSF software [ 29 , 30 ]. Briefly, it included removing the first 10 volumes, slice-timing, head motion realignment, brain tissue segmentation, spatial normalization, temporal filtering (0.01–0.10 Hz), and regressing out the signals from white matter, cerebrospinal fluid, and whole brain as well as the Friston-24 head motion parameters [ 31 , 32 ]. All images have been manually checked by trained researchers to ensure good quality.…”
Section: Methodsmentioning
confidence: 99%